## Related questions with answers

Transform the equation ${t(t - 1)y^{(4)} + e^{t}y'' + 4t^{2}y = 0}$ into an equivalent first order system.

Solution

VerifiedWe have the equation

$\begin{gather*} t(t - 1)y^{(4)} + e^{t} y'' + 4t^{2} y = 0, \end{gather*}$

and we have to transform it into an equivalent first order system by the following technique :

Let the functions

$\begin{gather*} x_{1} = y, \\ x_{2} = y', \\ x_{3} = y'', \\ x_{4} = y''', \end{gather*}$

and differentiate them with respect to $t$,

Then we have

$\begin{gather*} x'_{1} = y' = x_{2}, \tag{1} \\ x'_{2} = y'' = x_{3}, \tag{2} \\ x'_{3} = y''' = x_{4}, \tag{3} \\ x'_{4} = y^{(4)} = - \dfrac{e^{t}}{t(t - 1)} y'' - \dfrac{4t}{t - 1} y = - \dfrac{e^{t}}{t(t - 1)} x_{3} - \dfrac{4t}{t - 1} x_{1} \tag{4} \\ \end{gather*}$

Put equations (1), (2), (3) and (4) into a matrix type, then we have

$\begin{gather*} \begin{pmatrix}x_{1} \\ x_{2} \\ x_{3}\end{pmatrix}' = \begin{pmatrix}0 & 1 & 0 & 0 \\ 0 & 0 & 1 & 0 \\ -\dfrac{4t}{t - 1} & 0 & -\dfrac{e^{t}}{t(t - 1)} & 0\end{pmatrix} \ \begin{pmatrix}x_{1} \\ x_{2} \\ x_{3} \\ x_{3}\end{pmatrix} + \begin{pmatrix}0 \\ 0 \\ 0 \\ 0\end{pmatrix} \end{gather*}$

## Create a free account to view solutions

## Create a free account to view solutions

## Recommended textbook solutions

#### Fundamentals of Differential Equations

9th Edition•ISBN: 9780321977069Arthur David Snider, Edward B. Saff, R. Kent Nagle#### A First Course in Differential Equations with Modeling Applications

10th Edition•ISBN: 9781111827052 (2 more)Dennis G. Zill#### Differential Equations: An introduction to Modern Methods and Applications

3rd Edition•ISBN: 9781118981221James R. Brannan, William E. Boyce#### Differential Equations with Boundary-Value Problems

9th Edition•ISBN: 9781305965799 (3 more)Dennis G. Zill## More related questions

- physical science

1/4

- physical science

1/7